Low level of growth of the Ecuadorian textile industry: High industrial concentration or structural production problems? - Amaluisa Peñaranda, Sebastián (2019)
The textile industry, which historically has been relevant for the Ecuadorian economy because of its influence in macroeconomics aggregates such the Gross Domestic Product (GDP) and the employment, has growth problems reflected in its production level. The objective of this article is to determine the principal cause of the low level of growth of this industry; for this reason, it will be checked the relationship between the industrial concentration and the level of growth of the industry. On the other hand, it will be determined the existence of entry barriers and productive problems that the Ecuadorian textile industry faces on, like causes of its low level of growth. In this article, it will be developed a qualitative and quantitative research. The principal results are that the textile industry presents a low level of industrial concentration and the entry barriers are not strong, for this reason, both do not have a direct influence in the low level of growth of the industry. Nevertheless, the Ecuadorian textile industry has structural problems derived from the industrial activities of the enterprises and the public policy. These problems are the principal cause of the growth problems of the industry. DOI: https://doi.org/10.31164/bcoyu.21.2019.691 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/691